Indonesian Societas Verbi Divini (SVD) Missionaries in the Netherlands - Fransiska Widyawati (DIEGESIS: Jurnal Teologi Kharismatika, 2026)
This article examines the deployment of Indonesian Societas Verbi Divini (SVD) missionaries to the Netherlands as a structured expression of "reverse mission," situating this contemporary phenomenon within a historical relationship spanning over a century. Based on fieldwork conducted in 2025, including semi-structured interviews with six Indonesian SVD priests currently serving in the Netherlands and participant observation in Dutch parishes, this study identifies 83 Indonesian missionaries active throughout the country, with the SVD emerging as the most numerically prominent male congregation. The article further argues that the current movement of Indonesian SVD missionaries to the Netherlands is not a spontaneous response to modern clerical shortages, but rather the latest chapter in a reciprocal relationship that began when Dutch SVD missionaries arrived in Indonesia in 1914. This reverse mission embodies a living theology of reciprocity, wherein the fruits of past evangelization return to revitalize an increasingly secularized Church. These findings contribute to the field of missiology by highlighting structured religious orders, rather than diaspora communities, as the primary institutional vehicles for reverse mission, and by demonstrating that historical missionary ties fundamentally shape contemporary currents of reverse mission. Abstrak Artikel ini mengkaji penempatan misionaris Societas Verbi Divini (SVD) Indonesia ke Belanda sebagai ekspresi terstruktur dari misi balik, menempatkan fenomena kontemporer ini dalam hubungan historis yang berlangsung lebih dari satu abad. Berdasarkan penelitian lapangan yang dilakukan pada tahun 2025, termasuk wawancara semi-terstruktur dengan enam imam SVD Indonesia yang saat ini melayani di Belanda dan observasi partisipan di paroki-paroki Belanda, studi ini mengidentifikasi 83 misionaris Indonesia yang aktif di seluruh negeri, dengan SVD sebagai kongregasi pria yang paling menonjol secara numerik. Artikel ini selanjutnya menyatakan bahwa pergerakan misionaris SVD Indonesia ke Belanda saat ini bukanlah respons spontan terhadap kekurangan pendeta modern, tetapi merupakan babak terbaru dari hubungan timbal balik yang dimulai ketika misionaris SVD Belanda tiba di Indonesia pada tahun 1914. Misi balik ini mewujudkan teologi timbal balik yang hidup di mana buah dari penginjilan masa lalu kembali untuk memperbarui Gereja yang semakin sekuler. Temuan ini berkontribusi pada kajian misiologi dengan menyoroti ordo keagamaan yang terstruktur, alih-alih komunitas diaspora, sebagai wahana kelembagaan utama misi balik, dan dengan menunjukkan bahwa ikatan misionaris historis secara mendasar membentuk arus misi balik kontemporer.